O "Brasil Trágico" de Sylvio Floreal: uma viagem pelo Mato Grosso (Revista de História Regional, 2020)
After three years of publishing Ronda da meia noite – vícios, misérias e esplendores da cidade de São Paulo [Midnight Round – vice, misery and splendors of São Paulo City], work that conferred the writer Domingos Alexandre, known by the pseudonym Sylvio Floreal, notoriety in the literary circles of Sao Paulo, a new publication is released, precisely in 1928, O Brasil Trágico – impressões, visões e mysterios de Matto Grosso (The Tragic Brazil – impressions, visions and mysteries of Mato Grosso). In it, the author gathers a series of texts written between July 1926 and July 1927, when he toured the state of Mato Grosso, lecturing, holding meetings, writing and stablishing professional contacts with members of intellectual elites and local politics, especially in the capital, Cuiabá. Such accounts, which will be analyzed in the present paper, directly dialogue with visions and idealizations that circulated in printed media about the so-called Brazilian hinterlands, revealing tensions and ambiguities between the desires for modernity that emanated from the largest national urban centers, specially Sao Paulo and Rio de Janeiro, and the hard reality faced by pioneer populations that, propelled by the 1920 agricultural expansion, would enter the vast countryside areas, yet unexplored and more often than not, unknown.